2014
DOI: 10.1007/s11033-014-3466-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum microRNA-195 is down-regulated in breast cancer: a potential marker for the diagnosis of breast cancer

Abstract: MicroRNA-195 (miR-195) is a tumor suppressor that plays an important role in tumorigenesis. There are few studies on miR-195 expression in breast cancer patients and the results have been inconsistent; therefore, this study examined miR-195 expression in the serum of BC patients. Samples from 102 normal subjects and 210 subjects with BC who had detailed clinical follow-up information available were selected. An internal reference (miR-16) and serum miR-195 were amplified and quantitatively detected by SYBR gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 50 publications
0
45
0
1
Order By: Relevance
“…It was found that serum miR-195-5p was significantly over-expressed in BC patients, and was associated with some biopathological features, such as histologic type and grade. Patients with lobular and poorly differentiated tumors had higher se- However, some other studies indicated decreased miR-195 levels compared to controls [30,31]. Interestingly, it was also found that miR-195 expression had a significant relationship with IGF-I and IGF-II.…”
Section: Discussionmentioning
confidence: 95%
“…It was found that serum miR-195-5p was significantly over-expressed in BC patients, and was associated with some biopathological features, such as histologic type and grade. Patients with lobular and poorly differentiated tumors had higher se- However, some other studies indicated decreased miR-195 levels compared to controls [30,31]. Interestingly, it was also found that miR-195 expression had a significant relationship with IGF-I and IGF-II.…”
Section: Discussionmentioning
confidence: 95%
“…Similar with other miRNAs, the expression patterns and functions of miR-195 may both be different in various types of cancer with a tissue-specific manner. For example, Zhao et al [16] reported that serum miR-195 was downregulated in breast cancer and was a potential marker for the diagnosis of this disease; Guo et al [17] demonstrated a tumor suppressive role of miR-195 in nonesmall cell lung cancer; Wang et al [18] indicated that miR-195 had a suppressive role in colorectal cancer and was able to inhibit cancer cell proliferation, colony-formation, and invasion. In contrast, Zanette et al [27] using the TaqMan miRNA assays identified miR-195 as one of highly expressed miRNAs in chronic lymphocytic leukemias.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have indicated that miR-93, miR-195, and members of the let-7 family of miRs are downregulated in lung cancer, CRC, and melanoma tissues as compared with normal tissue, suggesting that these miRs are tumor suppressors [29][30][31][32][33][34][35][36][37]. miR-93 can suppress the proliferation of human colon cancer cells and colon cancer stem cells, with worse OS being associated with low miR-93 expression in CRC patients [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…miR-93 can suppress the proliferation of human colon cancer cells and colon cancer stem cells, with worse OS being associated with low miR-93 expression in CRC patients [37,38]. miR-195 can suppress tumor cell proliferation and metastasis by targeting several proteins, including BCOX1, BCL-2, and CARMA3 [32][33][34]. The overexpression of let-7b in vitro can downregulate cell-cycle-related proteins, including cyclin D1, cyclin D3, cyclin-dependent kinase 4, and the high-mobility group protein and oncogene [30,39].…”
Section: Discussionmentioning
confidence: 99%